A narrative review of evidence to guide deprescribing among older adults. (28th May 2021) - Ie, Kenya; Aoshima, Shuichi; Yabuki, Taku; Albert, Steven M.
Abstract: Potentially inappropriate prescription and polypharmacy are well‐known risk factors for morbidity and mortality among older adults. However, recent systematic reviews have failed to demonstrate the overall survival benefits of deprescribing. Thus, it is necessary to synthesize the current evidence to provide a practical direction for future research and clinical practice. This review summarizes the existing body of evidence regarding deprescribing to identify useful intervention elements. There is evidence that even simple interventions, such as direct deprescribing targeted at risky medications and explicit criteria‐based approaches, effectively reduce inappropriate prescribing. On the other hand, if the goal is to improve clinical outcomes such as hospitalization and emergency department visits, patient‐centered multimodal interventions such as a combination of medication review, multidisciplinary collaboration, and patient education are likely to be more effective. We also consider the opportunities and challenges for deprescribing within the Japanese healthcare system. Abstract : This review summarizes the existing body of evidence regarding deprescribing to identify useful intervention elements. There is evidence that even simple interventions, such as direct deprescribing targeted at risky medications and explicit criteria‐based approaches, effectively reduce inappropriate prescribing. On the other hand, if the goal is to improve clinical outcomes such as hospitalization and emergency department visits, patient‐centered multimodal interventions such as a combination of medication review, multidisciplinary collaboration, and patient education are likely to be more effective.